Indicadores de desempenho e percepção subjetiva de esforço entre técnico e atletas de voleibol - Borin, João Paulo; Dias, Rodrigo de Godoy; Leite, Gerson dos Santos; Padovani, Carlos Roberto Pereira; Padovani, Carlos Roberto [UNESP] (My University, 2010)
The present study has for objective been to know the answers of performance indicators between different positions of volleyball and check for possible relationship between subjective perception referred by coach effort of volleyball athletes during training. Eleven athlete of the feminine sex, during eight weeks, 23 carried through sessions of training and eleven games, inferior members (Vertical Jump) and superiors had been evaluated by means of measures of explosive power in (Throw Medicine Ball), at the beginning and end of each week. For the verification of the subjective perceived of exertion it was used scales proposal for Foster (1998), to the end of each session of training. The collected data had been kept in computer file, producing information in the descriptive plan (measured central and dispersion) and the inferencial for the analysis of variance for the model with a factor complemented with the test of multiple comparisons of Tukey and linear correlation of Pearson. The results present as it has detached: i) the exercises specifics as content of bigger frequency in the training; ii) the test of vertical jump presented difference between the positions and, finally, iii) the subjective perceived of exertion between coach and athlete, he points that the trainer overestimates in 9,76% the perceived of the athletes. Such data are argued how much to the contents of the training as well as the load used in the interior of the process of preparation and monitoring of the training.

O presente trabalho objetivou conhecer as respostas de indicadores de desempenho entre diferentes posições do voleibol e verificar uma possível relação entre a percepção subjetiva de esforço referida pelo técnico e a relatada pelas atletas de voleibol durante os treinamentos. Onze atletas do sexo feminino, durante 23 sessões de treinamento e 11 jogos, foram avaliadas por meio de medidas de força explosiva em membros inferiores (Salto Vertical) e superiores (Arremesso de Medicine Ball-AMB), no início e final de cada semana. Para a verificação da percepção subjetiva de esforço (PSE) utilizou-se a escala proposta por Foster (1998), ao final de cada sessão de treinamento, tanto para o técnico como para as atletas. Os dados coletados armazenados em banco computacional produziram informações no plano descritivo (medidas de centralidade e dispersão) e inferencial (análise de variância para o modelo com um fator complementado com o teste de comparações múltiplas de Tukey e cálculo do coeficiente de correlação linear de Pearson). Os resultados apresentaram como destaque: i) os exercícios especiais como o conteúdo de maior freqüência nos treinamentos; ii) diferença significativa entre as posições em relação ao salto vertical e, por fim, iii) a relação funcional da percepção subjetiva de esforço entre técnico e atleta, apontam que o primeiro superestima em 9,76% a das atletas. Tais dados são discutidos quanto aos conteúdos do treinamento bem como a carga utilizada no interior do processo de preparação desportiva e monitoramento do treinamento.
Performance indicators and subjective perception effort between coach and volleyball athletes
Keywords: Training; Preparation; Volleyball; Treinamento desportivo; Preparação; Voleibol